Wordlength effect on CMA adaptive antenna with digital beam synthesis initialization - Boonpoonga, Akkarat; Tantisopharak, Tanawut; Sirisuk, Phaophak; Krairiksh, Monai (My University, 2008)
This paper investigates the wordlength effect on the CMA adaptive antenna with digital beam synthesis initialization. The antenna is a four-element circular array whose main beam can be switched into different directions by using digital beam synthesizer. A beam obtained from digital beam synthesis is exploited as an initial beam for CMA. A weight vector for generating initial beams of CMA is chosen by determining radiation patterns. The SINR of the digital beam synthesis-based CMA adaptive antenna with different wordlengths are shown. Moreover, the step-size constant of CMA is also investigated and properly chosen to avoid underflow and overflow phenomena. © 2008 IEEE.